Randomized controlled trials of digital health interventions for rheumatic disease management: a systematic review. - Santosa, Anindita; Weiquan Li, James; Tze Chin Tan (Bulletin of the World Health Organization, 2025)
Objective To evaluate the adoption, effectiveness and cost-effectiveness of digital health interventions for rheumatic disease management. Methods Between 25 May 2024 and 2 June 2024, we systematically searched PubMed®, Scopus, ClinicalTrials.gov, the Global Observatory for eHealth and the World Bank Open Knowledge Repository for randomized controlled trials (RCTs) evaluating digital health interventions for rheumatic disease management. We included studies published between 2000 and 2024 that reported on adoption rates and efficacy. Two reviewers independently screened the studies, extracted data and categorized the digital interventions according to the World Health Organization's classification of digital health interventions. Findings Of the 455 unique records identified, 21 RCTs met the inclusion criteria. Most digital health interventions (15 studies) focused on individual-centric interventions, such as targeted communication, personal health tracking, educational tools and wearable devices. Studies in high-income countries implemented advanced, integrated digital interventions combining individual-focused approaches with health worker interventions and data services using telemedicine platforms and decision support systems. In contrast, studies in low- and middle-income countries adapted accessible technologies such as mobile messaging and telephone-based education. Many telehealth, wearable technologies and educational interventions significantly improved disease control, patient adherence, knowledge and self-efficacy. Of the five studies assessing cost-effectiveness, all found digital interventions to be cost-effective. Conclusion Digital health interventions show promise for managing rheumatic diseases. Tailoring these interventions to local infrastructure and emphasizing patient engagement are crucial for successful adoption. Future research should focus on standardizing evaluation methods, addressing digital divides and enhancing provider support and data services.